Digital Marketing Design to Increase Tourism Visit and Maintain the City Image - Koeswandi, Tika Annisa; Fauziyah, Azizah; Nurfitriya, Mira (The International Journal of Business Review (The Jobs Review), 2020)
In 2020, the advance technology of business activity has come to the phase where the promotion is in a form of digital marketing. It promotes to a broader range of costumer. A design on how digital marketing affects the tourism visit and city image is needed. This research is descriptive qualitative research involving the implementation of digital marketing conducted by the City Government of Tasikmalaya and the Department of Tourism, Youth and Sports through the Tasik October Festival event. Data collection techniques was literature study and interviews with the organizers of the Tasik Oktober Festival event. The data were then analyzed descriptively using data triangulation techniques. This research found that a design of digital marketing that consists of quality website, strong social media presence, enganging content and mobile-friendly, a virtual brand awareness can be developed and product images can be built, this is because through digital media, old consumer and new consumer meetings can occur